2022
DOI: 10.3390/v14112480
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus: The Emergence of Genotype IV in Australia and Its Potential Endemicity

Abstract: A fatal case of Japanese encephalitis (JE) occurred in northern Australia in early 2021. Sequence studies showed that the virus belonged to genotype IV (GIV), a genotype previously believed to be restricted to the Indonesian archipelago. This was the first locally acquired case of Japanese encephalitis virus (JEV) GIV to occur outside Indonesia, and the second confirmed fatal human case caused by a GIV virus. A closely related GIV JEV strain subsequently caused a widespread outbreak in eastern Australia in 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 196 publications
(286 reference statements)
1
64
0
Order By: Relevance
“…These models allow the evaluation of spatial dependencies among JEV outbreaks in relation to landscape features and thus help to spatially demarcate risk. As a null model representing complete spatial randomness (CSR), JEV outbreaks were first fitted as a homogeneous Poisson process, with conditional intensity, λ(u,X) = β, [1] in which u represents outbreak (X) locations and β is the intensity parameter which signifies the number of points in a subregion of a defined spatial window. The expected intensity under CSR is simply proportional to the area of the subregion under investigation [57], indicating an absence of spatial dependency.…”
Section: Point Process Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…These models allow the evaluation of spatial dependencies among JEV outbreaks in relation to landscape features and thus help to spatially demarcate risk. As a null model representing complete spatial randomness (CSR), JEV outbreaks were first fitted as a homogeneous Poisson process, with conditional intensity, λ(u,X) = β, [1] in which u represents outbreak (X) locations and β is the intensity parameter which signifies the number of points in a subregion of a defined spatial window. The expected intensity under CSR is simply proportional to the area of the subregion under investigation [57], indicating an absence of spatial dependency.…”
Section: Point Process Modellingmentioning
confidence: 99%
“…Japanese encephalitis virus (JEV) re-emerged in Australia over the 2021-2022 summer with extensive outbreaks in piggeries and sporadic cases in humans manifesting an unprecedented geographic distribution across Queensland, New South Wales (NSW), Victoria, and South Australia [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of JE in humans caused by GIV JEV infection was reported in 2019 [ 31 ]. The endemics of JE in Australia in 2021 and 2022 were also caused by GIV JEV [ 38 , 39 , 40 ]. However, only a few GIV JEV have been isolated before the epidemics, little attention has been paid to GIV JEV, and GIV JEV has not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of the JEV isolates from mosquitoes and pigs indicated that the isolates in 1998 also belonged to GII, whereas the isolate from Badu in the Torres Strait Islands in 2004 belonged to GI [ 36 , 37 ]. A JE patient who was thought to be infected with GIV JEV in the Tiwi islands in northern Australia was confirmed as infected in Australia in 2021 following a 20-year absence of JE [ 38 , 39 , 40 ]. In 2022, JEV was widespread in Australia.…”
Section: Introductionmentioning
confidence: 99%